Systematic positions and taxonomy of two freshwater ciliates found in China, with establishments of one new family and two new species (Ciliophora, Oligohymenophorea) - Xiang Wang; Lihui Liu; Jialu Wang; Xiaosong Wang; Jiarui Wang; Li Wang; Lv Zhao; Xuming Pan (European Journal of Taxonomy)
The morphology and molecular phylogeny of two freshwater ciliates, Pseudotetrahymena orientalis gen. et sp. nov. and Cyclidium paravorax sp. nov., collected from Harbin, Northeast China, were investigated based on morphology of live specimens and ciliary pattern; the phylogenetic placements were inferred from the SSU-rRNA gene. Pseudotetrahymenidae fam. nov., assigned to the order Tetrahymenida Fauré-Fremiet in Corliss, 1956, can be distinguished from the other families by its membranelle 2 consisting of several clusters and the shape of the cell. The new species C. paravorax is similar to C. vorax Pan, 2020 in most morphological features except the membranelle 3, which is single-rowed. Phylogenetic analyses based on SSU-rRNA gene sequence indicate that Pseudotetrahymenidae lies in the periphery of the Tetrahymenida clade and forms an independent, fully supported clade. Cyclidium paravorax groups with C. glaucoma Müller, 1773, which supports the assignment of the new species to the genus Cyclidium Müller, 1773.